Biomechanical Properties of 3D-Printed Cervical Interbody Fusion Cage With Novel SF/nHAp Composites - Shuang Chen; Yi Meng; Guozhi Wu; Zhize Liu; Xiaodong Lian; Jianyu Hu; Dongfang Yang; Guiqi Zhang; Kun Li; Hao Zhang (Frontiers in Materials, 2021)
Anterior cervical discectomy and fusion (ACDF) is a commonly used surgical method for the treatment of cervical spondylosis. As ACDF surgery is widely used in clinics, identifying suitable materials to design and prepare cervical interbody fusion cages is a hot research topic. Here, we describe a new three-dimensional (3D) printing approach to create stretchable and tough silk fibroin/nano-hydroxyapatite (SF/nHAp) composites with tunable mechanical properties. The compressive strength of the novel composites with biomimetic structure could reach more than 128 MPa. More importantly, the composites were prepared using 30% silk fibroin and 70% hydroxyapatite, a composition similar to the human bone tissue. Finite element analysis results indicate that the stress distribution of SF/nHAp composite cervical interbody fusion cages in vivo is more uniform than that of commercial Ti alloy cages. This study evaluates the effectiveness of SF/nHAp composites for application in cervical interbody fusion cages and in the field of bone tissue engineering.